Regresividad de derechos en la aplicación del Código Orgánico de las Entidades de Seguridad Ciudadana y Orden Público en las instituciones complementarias de seguridad - Zambrano Menéndez, José Michael (2023)
The objective of this research work is to analyze the regressivity of rights in the application of the Organic Code of Citizen Security and Public Order Entities in complementary security institutions. It began with a theoretical compilation of the concepts that encompass the two variables under study, such as the regressivity of rights and the application of the Organic Code of Citizen Security and Public Order Entities, then 5 interviews were applied to people who know the subject. mentioned and that are part in one way or another of the institutions involved in the change of labor regime and 30 surveys of workers with the denomination firefighters and municipal control agents. Among the main results, which are detailed in depth in title 7, it was found that there is a regressivity of rights, since rights and social benefits that today are not considered in the Organic Code of Citizen Security and Public Order Entities. the workers contemplated under the nominative firefighters and municipal control agents, have been receiving in their monthly role, the payment of extraordinary hours is not guaranteed, in addition, if there is no salary scale where the lit. 2 of art. 23 of the universal declaration of human rights, which states "everyone has the right, without discrimination, to equal pay for equal work" Keywords: Organic Code, Citizen Security, Public Order, social benefits,